Internal R&D and external information in knowledge-intensive business service innovation: complements, substitutes or independent? - Doloreux, David; Shearmur, Richard; Rodriguez, Mercedes (Technological and Economic Development of Economy, 2018)
This paper analyses the effect of internal R&D and of external sources of information on the innovation performance of Knowledge intensive business services (KIBS). The analysis is based on an establishment-level survey covering the period of 2011–2014 in Canada (Quebec). In order to determine the influence of different external information sources on innovation and the extent to which internal R&D and the use of external information sources are related to innovation, a series of logistic regressions are performed on four different measures of innovation. The results show that KIBS innovation is positively connected to market-related information sources (but not to research and academic sources), that KIBS innovation is positively associated with the performance of R&D, and that there are no synergies associated with the combined performance of R&D and external information gathering: their effects are independent and additive. These results share some similarities, but also some important differences, with those that have been obtained from the study of R&D and external information sourcing in manufacturing establishments.